Socioeconomic Position and Picky Eating Behavior Predict Disparate Weight Trajectories in Infancy - Galloway, Amy T.; Watson, Paul; Pitama, Suzanne; Farrow, Claire V. (Frontiers in Endocrinology, 2018)
Infant weight gain has long-term implications for the establishment of overall health. We examined whether socioeconomic position (SEP), the use of pressure as a feeding practice, and picky eating relate to changes infant in weight-for-length (WFL). A sequential design was used to examine whether current levels of child picky eating, parental use of pressure, and SEP were associated with changes in WFL during infancy. Health providers distributed survey packets during routine well-child visits made in the homes of families with young children in New Zealand (n = 193). Primary caregivers of young children provided their child’s current level of picky eating, their use of pressure, and their SEP. They also reported their child’s professionally-measured WFL from birth, 8, 15 and 21 months of age. A multi-level modeling analysis yielded an interaction between SEP and picky eating in predicting infant weight change over time. Children who had a low SEP and were not picky eaters were on the highest WFL trajectory and children who had a low SEP and were picky eaters were lowest on the WFL trajectory. A main effect revealed that higher levels of parental pressure predicted lower WFL in infants at each age, but did not interact with SEP or picky eating. Findings from this study indicate that the combination of eating behavior and SEP are associated with differential infant growth patterns. These results suggest that eating behavior and SEP should be included in the development of interventions designed to achieve healthy weight during childhood.